Toll collection and economic development in twelfh-century Flanders - Bonduel, Elisa (TSEG - The Low Countries Journal of Social and Economic History, 2024)
The twelfth century is generally considered as a period of economic growth and trade intensification in Europe. This commercial development was characterised by a revival of long-distance trade, a growth of trade volumes and a diversification of commodities. Due to the source bias, many historians have, however, attributed a rather peripheral role to Northwestern Europe in this narrative. Notably, the exact chronology and character of this commercial development in a fast developing region like coastal Flanders has long been disregarded by historians. By deploying sources on toll collection, more specifically toll exemptions and tariffs, this paper aims to expand our understanding of this process in this region.